2019
DOI: 10.3390/v11060496
|View full text |Cite
|
Sign up to set email alerts
|

The Adenosine Analogue NITD008 has Potent Antiviral Activity against Human and Animal Caliciviruses

Abstract: The widespread nature of calicivirus infections globally has a substantial impact on the health and well-being of humans and animals alike. Currently, the only vaccines approved against caliciviruses are for feline and rabbit-specific members of this group, and thus there is a growing effort towards the development of broad-spectrum antivirals for calicivirus infections. In this study, we evaluated the antiviral activity of the adenosine analogue NITD008 in vitro using three calicivirus model systems namely; f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Accordingly, we investigated the in vitro efficacy of three antiviral compounds (NTZ, 2CMC, NITD-008) against representative strains of FCV-VSD. These molecules have demonstrated antiviral activity against the F9 vaccine strain with EC50s values in the low micromolar range [15], and showed dose-response inhibition against the replication of FCV-VSD strains at low micromolar concentrations. Nucleoside analogues, 2CMC and NITD-008, inhibit the viral RNA-dependent RNA polymerase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, we investigated the in vitro efficacy of three antiviral compounds (NTZ, 2CMC, NITD-008) against representative strains of FCV-VSD. These molecules have demonstrated antiviral activity against the F9 vaccine strain with EC50s values in the low micromolar range [15], and showed dose-response inhibition against the replication of FCV-VSD strains at low micromolar concentrations. Nucleoside analogues, 2CMC and NITD-008, inhibit the viral RNA-dependent RNA polymerase.…”
Section: Discussionmentioning
confidence: 99%
“…4). NTZ showed a half maximal cytotoxic concentration (CC50) value of 12.7 µM, whilst 2CMC and NITD-008 demonstrated CC50 values of >100 µM [14,15]. Therefore, using the higher EC50 values obtained for each compound, the therapeutic index (TI = CC 50 /EC 50 ) values determined for NTZ, 2CMC and NITD-008 were 21, >18 and >111, respectively (Figure 3).…”
Section: Antiviral Compound Efficacymentioning
confidence: 97%
See 1 more Smart Citation
“…NITD008, fexaramine and 2CMC are also candidate drugs to treat FCV infection. NTZ and 2CMC have been shown to have synergistic anti-FCV activity, and have been used to treat FCV-infected cats (Enosi Tuipulotu et al, 2019;Fumian et al, 2018;Kim and Chang, 2018). MZR has been shown to have antiviral activity against caprine alpha herpes virus 1 (CpHV-1), but it had not been determined whether it also has activity against FCV (Camero et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al showed that 2CMC triphosphate (2CMC-TP) inhibited the viral polymerases by competing directly with natural CTP during primer elongation, therefore acting as a classic chain terminator [ 139 ]. 7-deaza-2′ -C- methyladenosine (7DMA) and NITD008 are adenosine analogues that were initially developed as an inhibitor of HCV and dengue virus replication, respectively, but also possess anti-NoV activity [ 40 , 140 ].…”
Section: Antiviral Targets and Known Antiviralsmentioning
confidence: 99%